DEVELOPING A JUNIOR HIGH SCHOOL GEOMETRY LEARNING KIT THAT SUPPORTS CHARACTER EDUCATION - Tanri Mega Sanjaya (Universitas Mercu Buana Yogyakarta, 2016)
This research aims to develop an Junior High School mathematics learning kit that supports character education, consisting of reasonable syllabus, lesson plan, worksheets, quizzes, and learning achievement test (THB). The research consists of five phases: (1) need analysis and objectives formulation, (2) design/product development, (3) product trial out, (4) product revision, and (5) final product evaluation. The results of the needs analysis show that learning kits that support the students' mathematical competence, especially geometry needs to be increased. While the character education is an important element in the the students personality formation, so the products develop to support character education, that consist of syllabus, lesson plan, worksheets, quizzes, and THB. The trials evaluation of the research are conducted by an expert judgment, small trials, and field trials. The subject of the research are 31 grade seven students of the First Public Junior High School of Pundong. The result of this study shows that the products is reasonable to be used. This result can be seen from the result of expert validation that the product is valid, the teacher assessment, students’ feedback, learning implementation observation percentage which show that the product meets with the practical criteria and the result of product implementation produce students to attain the minimum completeness criteria and have characters development which show that the product is effective. Keywords: development, learning kit, character education